2012
DOI: 10.1080/00918369.2012.673945
|View full text |Cite
|
Sign up to set email alerts
|

Gay Officers In Their Midst: Heterosexual Police Employees' Anticipation of the Consequences for Coworkers Who Come Out

Abstract: While fear among gay men and lesbians about being out in a masculinist environment is not surprising, this article examines what heterosexuals expect will happen when gay men and lesbians come out. We draw on a unique dataset from a police department in the southwest United States to examine the consequences anticipated by heterosexual police department employees if a gay or lesbian officer's sexual orientation became known in the workplace. We test four main sets of factors: individual-level demographic chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 36 publications
0
20
0
1
Order By: Relevance
“…Conversely, a gay LEO might choose not to come out at work because he perceives that rules are sometimes applied inequitable across sexual orientations, with gay men being more harshly regulated than heterosexual men. This reason for remaining in the closet extends prior scholarship that merely indicates homophobia as one of the primary perceived reasons gay officers have for staying the closet (Bernstein & Swartwout, ) by providing a more clear picture of one way that homophobia becomes manifest in LE: through the application of policy in a questionable, yet legally defensible, manner.…”
Section: Critical Discussion Of Interpretation and Implications Of Thmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, a gay LEO might choose not to come out at work because he perceives that rules are sometimes applied inequitable across sexual orientations, with gay men being more harshly regulated than heterosexual men. This reason for remaining in the closet extends prior scholarship that merely indicates homophobia as one of the primary perceived reasons gay officers have for staying the closet (Bernstein & Swartwout, ) by providing a more clear picture of one way that homophobia becomes manifest in LE: through the application of policy in a questionable, yet legally defensible, manner.…”
Section: Critical Discussion Of Interpretation and Implications Of Thmentioning
confidence: 99%
“…Symbolic elements of LE's organizational culture are particularly important because they may influence and shape the conditions of the work as something certain people (i.e., gay men or women or people of Color) are perceived as less capable of doing. For example, Bernstein and Swartout () found that amongst police employees, “characteristics of workplaces, measured by tolerance and discrimination, as well as contact with gay men and lesbians on the job are more significant predictors of anticipated outcomes [related to coming out] than are individual‐level traits and attitudes” (p. 1147). This means that the actual feel and sophistication of law enforcement agencies influences the extent to which gay men and lesbians are likely to exercise disclosure and to feel comfortable, thus making them an important site for HRD research and intervention.…”
Section: Disclosure and Coming Outmentioning
confidence: 99%
“…Some officers may choose to disclose their sexual identity to colleagues and/or the organization, while others may choose to conceal this part of their identity to avoid differential treatment (Bernstein & Kostelac, 2002; Colvin, 2014). There is a wide body of literature which examines disclosure of sexuality in the workplace and how this affects police officers (see Bernstein & Swartwout, 2012; Miller et al, 2003). The diversification of police organizations has created opportunities for recruitment of officers from diverse groups, yet critics argue members of the LGBTIQ+ community who join police agencies remain significantly underrepresented within police organizations (Workman-Stark, 2015) and (when discovered to self-identify with the LGBTIQ+ community) are often relegated to liaison roles or police work considered “less dangerous” or “less manly.”…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, despite her years of experience and success as a law enforcement officer, when Kimberly Jacobs was named Chief of Police in Columbus, Ohio many commenters on the Columbus Dispatch website questioned her competency and sexuality. Several asserted the move was political in nature, an especially concerning charge given that women comprise less than 2 percent of police chiefs nationwide (Caruso ; see also Bernstein and Swartwout ). Jacobs's story is but one example of how occupational culture and its defense play out in the lives of LGBQ individuals engaged in police work.…”
Section: Forms and Sources Of Homophobia And Heterosexism: Individualsmentioning
confidence: 99%